THE ASSOCIATION BETWEEN VITAMIN D DEFICIENCY AND INSULIN RESISTANCE - Negmatova Gulzoda Shuhratovna; Usmonov Azimbek; Ibodullayev Avazbek; Shodiyev Dilmurod (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract. Vitamin D deficiency is a widespread public health issue affecting over one billion people worldwide and has increasingly been linked to insulin resistance and type 2 diabetes mellitus. Vitamin D acts through the vitamin D receptor (VDR), which is expressed in pancreatic β-cells, skeletal muscle, adipose tissue, and the liver-tissues essential for glucose metabolism. Several mechanisms may explain this association, including impaired β-cell function and insulin secretion, disrupted calcium homeostasis, increased systemic inflammation, and altered expression of genes involved in insulin signalling. Epidemiological studies have consistently reported an inverse relationship between serum 25-hydroxyvitamin D levels and insulin resistance, commonly assessed using HOMA-IR. Although intervention trials have shown mixed findings, vitamin D supplementation appears to improve insulin sensitivity and glycaemic control in individuals with established deficiency. This review summarises current evidence on the relationship between vitamin D deficiency and insulin resistance and considers the potential role of vitamin D supplementation in prevention and management strategies.